Distribuição de células-tronco adulta humana em diferentes fases do desenvolvimento dentário: uma análise metodológica dos constituintes histológicos - Carvalho, Stephany Pimenta (2019)
Tissue loss and the reestablishment of its function is challenging in regenerative medicine. A cellular subpopulation, called adult stem cells, is fundamental in tissue repair. These cells are capable of self-renewal and differenciation, playing an important role in tissues regenerative process in the whole organism. Dental structures are promising sources of these cells for easy access. The distribution of adult stem cells in dental structures is still poorly understood. Dental pulp removal for laboratory studies still faces methodological impasse due to the lack of protocol standardization. The aim of this study was to topographically locate adult pulp stem cells and from dental associated structures at various stages of dental development and to evaluate the effectiveness of tissue collection methods. Adult pulp and dental associated tissues stem cells were identified by immunostaining and gene expression in human deciduous and permanent teeth at various stages of development. For the topographic study, 35 teeth were obtained: 8 deciduous teeth, 12 open-apex permanent teeth, 5 closed-apex permanent teeth and 10 pericoronal follicles. After extraction, teeth were decalcified in pH 7.0 EDTA solution and cut out for immunohistochemical analysis with CD10, CD44, CD90, Nanog and Oct-3/4 monoclonal antibodies. For gene expression study, fresh tissues were obtained by enzymatic digestion with 3 mg/ml type IV collagenase. Tissue preservation analysis was performed in 3 open-apex permanent teeth sectioned in the cementoenamel junction. To remove dental pulp, two methods were followed: mechanical removal with endodontic file or unhandled dental pulp enzymatic digestion. The results showed differential presence of stem cell markers in dental structures and topographic constituents. CD44 was expressed exclusively in odontoblastic layer of open-apex permanent teeth at root region. Pulp and dental associated tissue capillary vessels and peripheral nerves expressed CD90 as well as in cementoblasts and periodontal ligament fibers. Only fibroblasts from dental papilla were positive for CD10, confirmed by RT-PCR. No expression was observed by transcriptional pluripotency factors Nanog and Oct-3,4. unhandled dental pulp enzymatic digestion was more effective in removing cellular constituents from dental pulp. The maintenance of odontoblastic layer was compromised by mechanical method. This study showed distinct topographic distribution of adult stem cell subpopulations in various stages of dental development. Permanent teeth with incomplete rhizogenesis appear to be a potential source of adult stem cells in in vitro studies. Choosing appropriate methods for dental pulp removal is essential for preserving its stem cell subpopulations, and unhandled dental pulp enzymatic digestion is more effective than mechanical method.